Fingerprinting a Number of Prunus Persica Varieties Cultivated In Duhok Province Using Srap Markers. - Ali, Avesta M.; Zubair, Sabrya J.; Sinjare, Dalal K.; Jubrael, Jaladet M. S. (Science Journal of University of Zakho, 2015)
In order to evaluate the genetic relationship among the germplasms of Prunus persica, sequence related amplified polymorphism (SRAP) marker was used to analyze genetic diversity of nine genotypes of peach cultivated in Duhok Governorate/ Kurdistan Region- Iraq. Twelve primer pairs generated 658 bands，379 bands were polymorphism; level of polymorphism observed in the present study with 12 primers pairs was 60.89 %. Revealed by NTSYS software the SM coefficient of genetic similarity ranged from 0.056 to 0.35. A dendrogram was constructed based on SRAP data using UPGMA cluster method. The nine genotypes of peach were classified into three groups and five sub-groups which were basically corresponded with the genetic relationships based on SRAP marker data.